Beyond n-dopants for organic semiconductors: use of bibenzo[d]imidazoles in UV-promoted dehalogenation reactions of organic halides - Tang, Kan; Brown, Megan R.; Risko, Chad; Gish, Melissa K.; Rumbles, Garry; Pham, Phuc H.; Luca, Oana R.; Barlow, Stephen; Marder, Seth R. (Beilstein Journal of Organic Chemistry, 2023)
2,2’-Bis(4-dimethylaminophenyl)- and 2,2'-dicyclohexyl-1,1',3,3'-tetramethyl-2,2',3,3'-tetrahydro-2,2'-bibenzo[d]imidazole ((N-DMBI)2 and (Cyc-DMBI)2) are quite strong reductants with effective potentials of ca. −2 V vs ferrocenium/ferrocene, yet are relatively stable to air due to the coupling of redox and bond-breaking processes. Here, we examine their use in accomplishing electron transfer-induced bond-cleavage reactions, specifically dehalogenations. The dimers reduce halides that have reduction potentials less cathodic than ca. −2 V vs ferrocenium/ferrocene, especially under UV photoexcitation (using a 365 nm LED). In the case of benzyl halides, the products are bibenzyl derivatives, whereas aryl halides are reduced to the corresponding arenes. The potentials of the halides that can be reduced in this way, quantum-chemical calculations, and steady-state and transient absorption spectroscopy suggest that UV irradiation accelerates the reactions via cleavage of the dimers to the corresponding radical monomers.
Keywords: dehalogenation; n-dopant; reduction; reductive dimerization